Pathological And Molecular Characterization Of A Dual Bacterial Co-Infection By Klebsiella Pneumoniae And Pseudomonas Aeruginosa In Juvenile European Goldfinches (Carduelis Carduelis) - Dr. Alessandra Vitale (Emerging Frontiers Library for The American Journal of Veterinary Sciences and Wildlife Discovery, 2025)
The present study reports the pathological and molecular characterization of a rare dual bacterial co-infection caused by Klebsiella pneumoniae and Pseudomonas aeruginosa in juvenile European goldfinches (Carduelis carduelis). Affected birds presented with clinical signs of respiratory distress, lethargy, anorexia, and progressive weight loss. Necropsy revealed severe pneumonia, hepatomegaly, and splenomegaly, while histopathological analysis confirmed extensive inflammatory infiltration and tissue necrosis in the lungs and liver. Bacteriological culture yielded both K. pneumoniae and P. aeruginosa, which were further confirmed by molecular identification using species-specific PCR assays. Antimicrobial susceptibility testing demonstrated multidrug resistance, highlighting the therapeutic challenges posed by these opportunistic pathogens. The dual infection likely exacerbated disease severity, contributing to rapid mortality in the flock. This case underscores the significance of considering mixed bacterial infections in avian pathology and emphasizes the need for accurate molecular diagnostics and prudent antimicrobial stewardship in avian medicine. Furthermore, the findings provide insights into the pathogenic synergy between K. pneumoniae and P. aeruginosa in passerine birds, with implications for wildlife health surveillance and conservation.